RELIGIOUS DEMOCRATIZATION IN INDONESIA: STRENGTHENING THE PRO-CEDURAL AND SUBSTANTIAL RELIGIOUS DEMOCRACY - Eka Hendry AR. (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
Inspired by the book of Michael Mann about the dark side of democracy that discusses the paradox between the ideality of democratic values and empirical realities of violence in the name of freedom (democracy), this paper begins with the exposure of the paradox, such as the rise of the violent conflict between groups of people (both ethnic and religious-based) and the high prevalence of violence between religious groups in Indonesia. Even worse, a very wrenching violence involves state actors (rulers). This paper tries to understand the roots of the paradox, with a look at how the relationship between state and religion and the religious community trend of Indonesia (especially Muslims). The author argues that the democratization of religion is a solution to the issues. To answer what kind of religious democracy lives in Indonesia, the author analyzes through a religious procedural (or constitutional) democratic dimension and religious substantial democratic dimension. The phenomenon of disobedience of law and system and the euphoria of law-making that reflects “intolerance” in several places in Indonesia display the fundamental issue in the religious procedural democracy. Whereas in the context of religious substantial democracy, the prevailing trend of religion that serves as a political and economic vehicle and ignores religion as a substantial aspect of the behavior of the Indonesian society has resulted in the marginalization of religious position and function. Then, the infiltration of the model of political Islam has also led to alienation of the character of the Islamic society of Indonesia, from a democratic pattern to a revival (radical) one. In this light, the author needs to present a strategy to encourage religious democracy in Indonesia, structurally through formulating the ideal relation model between state and religion and culturally through a substantial pattern of religion embedded with the character of Indonesian religious communities as well as the need to revitalize the true Indonesian Islamic model which will be intrinsically familiar with the principles of democracy. Key words: Democracy, religious procedural, substantial democracy, intolerance, law and system of disobedience.